GENDER EQUALITY DALAM PENYELESAIAN NUSYUZ PERSPEKTIF MASLAHAH DAN MUFASSIR - Irawan, Wahyudi; Neli, Jumni; Nur, Afrizal (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
This research is based on the problem of resolving Nusyuz. the term Nusyuz itself is the absence of harmony in the household caused by many factors between husband and wife. factors between husband and wife. The settlement of nusyuz settlement which is considered and accused of not promoting gender equality by feminists.by the femenism group. If the husband is worried that his wife is nusyuz, theThere are 3 stages of resolution based on the understanding of the reference Q.S An-Nisaa' verse 34 namely advising, bed separation and beating. While the wife is worried that her husband will commit nusyuz, then the solution step is based on the reference to Q.S An-Nisaa' verse 128 by making peace or giving up some of her rights in order to maintain the household. maintain the household. So this research aims to provide a comprehensive understanding understanding of the meaning and intent of the word of God related to the settlement of nusyuz. God's words related to the settlement of this nusyuz. So that the holy Qur'ran and Islam, a religion that prioritises gentleness, do not get out of line in understanding the meaning and intent of religion that prioritises gentleness is not accused of being the root of the problem of domestic violence. in this household. This research is pure literature, as The primary data source is from classical and contemporary tafsir books. The method The method used in this research is descriptive analytical method. From This research can be concluded that, first, nusyuz is on the husband and wife. wife. Both mufassirs agree to follow the steps of resolution offered by the Qur'an in sequence. by the Qur'an in sequence. Third, related to the step of hitting which is accused of gender bias by feminists mufassirs agree to provide signs if a beating occurs. All of these signs are made to maintain the absence of gender bias and the loss of women's dignity, such as the gender bias and the loss of women's dignity such as not making an impression, leave wounds, make injuries and not hitting the face. the face. the purpose of which is only for education and maintaining the sacred bond of marriage. So it can be concluded that the settlement of this nusyuz prioritises gender equality. gender equality).